Fuzzy Logic Based Clustering With Firefly Optimized Routing Protocol For Qos Aware Wireless Sensor Networks - et. al., S. Arockia Babi Reebha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowdays, Wireless sensor networks (WSN) becomes familiar due to its applicability in diverse areas of gathering and processing data from the physical environment. At the same time, the advanced applications and new multimedia sensors have raised the demand for highly sufficient management of their quality of service (QoS). The constraints and requirements for theQoS management entirely based on the application perspective. In this view, this paper presents a QoS aware cluster based routing (QoS-CR) technique for WSN. The proposed QoS-CR involves three main processes, namely clustering, routing and maintenance. At the earlier stage, fuzzy logic based clustering (FBC) technique gets executed to organize the nodes into clusters and selects cluster heads (CHs) effectively. Then, a firefly with a levy (FF-L) algorithm is employed for identifying the optimal paths between two CHs or CHs to BS. Finally, the maintenance process is invoked to balance the load and energy consumption throughout the network evenly. A detailed simulation analysis takes place to ensure the performance of the QoS-CR model, and the results are validated interms of several measures under a distinct number of nodes and simulation rounds. The outcome of the extensive simulation verified the superior characteristics of the proposed model over the compared methods.